2018
DOI: 10.3727/096504017x14912172235777
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Rap2B, a Ras Superfamily Protein, Inhibits Proliferation, Migration, and Invasion in Cervical Cancer Cells via Regulating the ERK1/2 Signaling Pathway

Abstract: Rap2B, belonging to the Ras superfamily, has been implicated in cancer development and functions as a tumor promoter. However, the role of Rap2B in cervical cancer is unknown. In this study, we investigated the expression pattern and biological functions of Rap2B in cervical cancer. The results showed that Rap2B was overexpressed in cervical cancer tissues and cell lines. Knockdown of Rap2B inhibited the proliferation, migration, and invasion of cervical cancer cells. In addition, our tumorigenesis assay showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The poor prognosis of patients with advanced cervical cancer is largely attributed to intrinsic molecular changes (2,3). During the growth and metastasis of cervical cancer, various oncogenes and tumor suppressors have been demonstrated to serve key roles, and some of these are suggested to become potential therapeutic targets for cancer treatment (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The poor prognosis of patients with advanced cervical cancer is largely attributed to intrinsic molecular changes (2,3). During the growth and metastasis of cervical cancer, various oncogenes and tumor suppressors have been demonstrated to serve key roles, and some of these are suggested to become potential therapeutic targets for cancer treatment (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Starch and glycogen can serve as energy reserves to sustain life. In addition, they can combine with other molecules to form glycoproteins, glycolipids and so on, 29 which play key roles in many biological basic activities such as cancer migration, 30 cell fusion, 31 protein function regulation 32 and embryo development. 33 Consequently, the recognition of carbohydrates in the medical, cell biology and other life sciences is of great significance.…”
Section: Carbohydrates Boronic Acid Sensorsmentioning
confidence: 99%
“…Then we further explored the downstream pathway of miR-1184, and we confirmed that miR-1184 could target RAP2B in BC. RAP2B has been reported to act as an oncogene, which increases cell proliferation, migration, and invasion in multiple tumors, like prostate cancer, hepatocellular carcinoma, and cervical cancer [33][34][35]. Furthermore, RAP2B promotes angiogenesis by activating the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/ vascular endothelial growth factor (VEGF) pathway in renal cell carcinoma [36].…”
Section: Discussionmentioning
confidence: 99%